Reign over me - 3 Arts Entertainment (Firm).; Madison 23 (Firm).; Mr. Madison Productions; Relativity Media; Sunlight Productions; Sony Pictures Home Entertainment (Firm). (Culver City, Calif. Sony Pictures Home Entertainment, 2007)
Alan Johnson runs into his old college roommate, Charlie Fineman, on the streets of New York City. He is surprised to find that Charlie does not remember him at all. Alan later learns that Charlie is suffering with grief over the loss of his family on 9/11. Flooded with grief, Charlie quits his job and isolates himself from everyone around him. Alan attempts to help Charlie get over his grief by rekindling their friendship. As Alan spends a lot of time with Charlie, it puts a strain on his relationship with his wife and kids.
Special features: Anamorphic widescreen version -- Behind the reign: The making of Reign over me -- Extended jam session with Adam Sandler and Don Cheadle -- A still reign: Photographic montage -- Language: English Dolby digital 5.1 ; Spanish Dolby digital 5.1 ; Thai Dolby digital 5.1 ; Portuguese Dolby digital 5.1 ; French Dolby surround -- Subtitles: Englihs, French, Spanish, Portuguese, Chinese, Korean, Thai.
Library has: VDR-1651 (2 DVDs)
Special features: Jam session with Adam Sandler and Don Cheadle; Behind the Reign: the making of Reign over me; and a still Reign: photographic montage.
Director of photography, Russ T. Alsobrook ; editors, Steve Edwards, Jeremy Roush ; music, Rolfe Kent ; costume designer, Deborah L. Scott ; production designer, Christian Wintter.
Adam Sandler, Don Cheadle, Jada Pinkett Smith, Liv Tyler, Saffron Burrows, Donald Sutherland, Robert Klein, Melinda Dillon, Mike Binder, Jonathan Banks.
DVD.
Keywords: Grief in men -- New York (State) -- New York -- Drama; Social isolation -- New York (State) -- New York -- Drama; Male friendship -- New York (State) -- New York -- Drama; Roommates -- United States -- Drama; September 11 Terrorist Attacks, 2001 -- Drama; New York (N.Y.) -- Drama; Melodrama